The PhenX Toolkit: Establishing Standard Measures for COVID‐19 Research. Issue 4 (27th April 2021) - Krzyzanowski, Michelle C.; Terry, Ian; Williams, David; West, Pat; Gridley, Lauren N.; Hamilton, Carol M.
Abstract: The PhenX (consensus measures for Phenotypes and eXposures) Toolkit (https://www.phenxtoolkit.org/ ) is a publicly available, web‐based catalog of recommended, well‐established measurement protocols of phenotypes and exposures. The goal of PhenX is to facilitate the use of standard measures, enhance data interoperability, and promote collaborative and translational research. PhenX is driven by the scientific community and historically has depended on working groups of experts to recommend measures for release in the PhenX Toolkit. The urgent need for recommended, standard measures for COVID‐19 research triggered the development of a "rapid release" process for releasing new content in the PhenX Toolkit. Initially, PhenX collaborated with the National Institutes of Health (NIH) Office of Behavioral and Social Sciences Research, the National Human Genome Research Institute, and the NIH Disaster Research Response (DR2) program to create a library of COVID‐19 measurement protocols. With additional support from NIH, PhenX adapted crowdsourcing techniques to accelerate prioritization and recommendation of protocols for release in the PhenX Toolkit. Prioritized COVID‐19‐specific protocols were used to anchor and define specialty collections of protocols that were subject to review and approval by the PhenX Steering Committee. In addition to the COVID‐19‐specific protocols, the specialty collections include existing, well‐established PhenX protocols, use of which will further enhance data interoperability and cross‐study analysis. The COVID‐19 specialty collections are Behaviors and Risks; Ethnicity, Race and Demographics; History, Treatment and Outcomes; Information Resources; Psychosocial and Mental Health; and Socioeconomic. The development and usage of PhenX COVID‐19 specialty collections are described in this article. © 2021 The Authors. Basic Protocol : Selecting COVID‐19 protocols